Taxonomic, nomenclatural, and faunistic records for species in tribes Melaenini, Moriomorphini, Pterostichini, Licinini, and Sphodrini (Coleoptera: Carabidae) - Guéorguiev, Borislav (Zootaxa, 2013)
Mexyclothorax baehri, sp. n. (type locality: Papua New Guinea, West Sepik Province, summit of Mount Capella, 3960 m), Atrotus indicus, sp. n. (type locality: India, Nilgiri Hills, Coonoor env.), Microzargus pakistanus, sp. n. (type locality: Pakistan, Kaghan Valley, Shogran env.) and Pterostichus (Oreophilus) podgoricensis, sp. n. (type locality: Montenegro, Podgoritsa env.) are described. The following nomenclatural acts are proposed: Hexagonia vartianorum Jedlička, 1967, syn. n. of Cymbionotum semirubricum (Reitter 1914); Poecilus (Derus) jarkendis (Jedlička, 1965), comb. n. of Pterostichus (Melanius) jarkendis Jedlička, 1965; Pterostichus (Pseudorthomus) namrun Jedlička, 1963, syn. n. of Amphimasoreus amaroides Piochard de la Brûlerie, 1875; Synuchus hummeli (Jedlička, 1935), comb. n. of Pterostichus hummeli Jedlička, 1935. In addition, new distributional records are recorded for Microzargus hartmanni Sciaky & Facchini, 1997, M. nepalensis Sciaki & Facchini, 1997 and Amphimasoreus amaroides.